Built environment assessment: Multidisciplinary perspectives - Karen Glanz; Susan L. Handy; Kathryn E. Henderson; Sandy J. Slater; Erica L. Davis; Lisa M. Powell (Elsevier, 2016)
Context: As obesity has become increasingly widespread, scientists seek better ways to assess and modify built and social environments to positively impact health. The applicable methods and concepts draw on multiple disciplines and require collaboration and cross-learning. This paper describes the results of an expert team׳s analysis of how key disciplinary perspectives contribute to environmental context-based assessment related to obesity, identifies gaps, and suggests opportunities to encourage effective advances in this arena. Evidence acquisition: A team of experts representing diverse disciplines convened in 2013 to discuss the contributions of their respective disciplines to assessing built environments relevant to obesity prevention. The disciplines include urban planning, public health nutrition, exercise science, physical activity research, public health and epidemiology, behavioral and social sciences, and economics. Each expert identified key concepts and measures from their discipline, and applications to built environment assessment and action. A selective review of published literature and internet-based information was conducted in 2013 and 2014. Evidence synthesis: The key points that are highlighted in this article were identified in 2014-2015 through discussion, debate and consensus-building among the team of experts. Results focus on the various disciplines׳ perspectives and tools, recommendations, progress and gaps. Conclusions: There has been significant progress in collaboration across key disciplines that contribute to studies of built environments and obesity, but important gaps remain. Using lessons from interprofessional education and team science, along with appreciation of and attention to other disciplines׳ contributions, can promote more effective cross-disciplinary collaboration in obesity prevention. Keywords: Obesity, Nutrition, Physical activity, Built environment, Interprofessional education